Acute Effects of Strength and Endurance Training on Bone Turnover Markers in Young Adults and Elderly Men - Stunes, Astrid Kamilla; Brobakken, Cathrine Langlie; Sujan, Md Abu Jafar; Aagård, Norun; Brevig, Martin Siksjø; Wang, Eivind; Syversen, Unni; Mosti, Mats Peder (Frontiers in Endocrinology, 2022)
Context: Exercise is recognized as an important strategy to prevent bone loss, but its acute effects on bone turnover markers (BTMs) and related markers remain uncertain. Objective: To assess the acute effects of two different exercise modes on BTMs and related markers in young adults of both sexes and elderly men. Design, Setting, Participants: A three-group crossover within-subjects design with a total of 53 participants, 19 young females (aged 22-30), 20 young males (aged 21-30 years) and 14 elderly males (aged 63-74 years), performing two different exercise sessions (strength training (ST) and high intensity interval training (HIIT)) separated by two weeks, in a supervised laboratory setting. Main Outcome Measures: Plasma volume corrected serum measurements of the BTMs C-terminal telopeptide of type 1 collagen (CTX-I) and procollagen of type 1 N-terminal propeptide (P1NP), total osteocalcin (OC), sclerostin and lipocalin 2 (LCN2) at baseline, immediately after, and 3 and 24 hours after each of the two exercise modes. Results and conclusion: Analyses revealed sex and age dependent differences in BTMs and related bone markers at baseline and time, sex and age dependent differences in response to exercise. No differences between exercise modes were observed for BTMs response, but for sclerostin in young males and for LCN2 in elderly males. An acute, transient, and uniform increase in P1NP/CTX-1 ratio was found in young participants, demonstrating that beneficial skeletal effects on bone metabolism can be attained through both aerobic endurance- and resistance exercise, although this effect seems to be attenuated with age. The acute effects of exercise on bone related biomarkers were generally blunted after 24 hours, suggesting that persistent alterations following prolonged exercise interventions should be assessed at later time points.